المسألة الكوانتية لأربع جسيمات في بُعد واحد (Latakia University Journal -Basic Sciences Series, 2018)
اخترنا في هذا البحث كمونات للتأثير المتبادل مناسبة (الكمون الصفري نصف القطر)، تسمح بتحديد مجال استخدام الطرق التقريبية التي تعكس الميزة الرئيسية على نحوٍ كامل لمسألة تشتت أربع بوزونات. وكذلك قمنا بفصل المتحولات واستخدمنا مؤثر شرودنغر الفعال منوهين إلى عدم استثناء حالة اقتراب الجسيمات الأربع من بعضها على مسافات صغيرة بشكل كاف. تم دراسة الحالات المرتبطة وتشتت أربع بوزونات متطابقة فلاحظنا أن الكمون يتناقص بسرعة كافية، كما أن لتشتت S- النصيب الأكبر في قيمة المقطع العرضي للطاقات المنخفضة. ثم حلت مسألة التشتت هذه عندما تكون المسافة بين أي بوزونين كبيرة والطاقة للحركة النسبية صغيرة، أما في حالة  كبيرة فيمكن استخدام تقريب بورن في حل المسألة. ثم أوجدنا الحل عند الطاقات العالية للحركة النسبية. We select in this research a suitable effect-exchanged potential (zero–range potential) that allowed us to define the range of approximately methods that reflect the main criteria of the full problem of scattering bosons. The variables have been separated and used an effected Schrodinger value regarding not-excluding approximate state for the four-particles from each other for adequate distances. We studied the related states and scattering the identical four-bosons. We note that the potential  decrease with a-none velocity. However s-scattering produce the bigger value in the low-energy cross-section. We solve the mentioned scattering problem when there is a big distance between any two bosons and the energy ε of the relative motion is small. However, in case the energy ε is big, it is possible to use Born approximate to solve the problem. Finally we find the solution of ultra energy for the relative motion.